2021
DOI: 10.1136/thoraxjnl-2021-217271
|View full text |Cite
|
Sign up to set email alerts
|

Breathlessness across generations: results from the RHINESSA generation study

Abstract: BackgroundBreathlessness is a major cause of suffering and disability globally. The symptom relates to multiple factors including asthma and lung function, which are influenced by hereditary factors. No study has evaluated potential inheritance of breathlessness itself across generations.MethodsWe analysed the association between breathlessness in parents and their offspring in the Respiratory Health in Northern Europe, Spain and Australia generation study. Data on parents and offspring aged ≥18 years across 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Parents reported the frequency and duration of physical activity of their child by answering two questions adopted from the RHINESSA study: “How often (How many hours per week) does your child usually do strenuous physical activity outside of school that makes her or him get out of breath or sweat more than usual (e.g., playing team sports, dancing, swimming, etc. )?” [ 45 , 46 ]. Response options for physical activity frequency were: Every day, 4–6 times per week, 1–3 times per week, At least once per month, Less than once per month, Never, and Don't know.…”
Section: Methodsmentioning
confidence: 99%
“…Parents reported the frequency and duration of physical activity of their child by answering two questions adopted from the RHINESSA study: “How often (How many hours per week) does your child usually do strenuous physical activity outside of school that makes her or him get out of breath or sweat more than usual (e.g., playing team sports, dancing, swimming, etc. )?” [ 45 , 46 ]. Response options for physical activity frequency were: Every day, 4–6 times per week, 1–3 times per week, At least once per month, Less than once per month, Never, and Don't know.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the duration of children's PA per week (None; <1 h; 1-2 h; 3-4 h; 5-6 h; >6 h), the parents were asked the following question: "Approximately how many hours per week does your child usually do strenuous PA outside of school that makes her or him get out of breath or sweat more than usual (e.g., playing team sports, dancing, swimming)?" This question was adopted from the RHINESSA study (Ekström et al 2022;Lindberg et al 2020).…”
Section: Covariatesmentioning
confidence: 99%
“… 39 Ekström et al found that breathlessness was nearly doubled in offspring of parents with breathlessness, even when adjusting for factors associated with breathlessness in both generations (obesity, smoking, depression, asthma, lower lung function and female sex). 40 Carsin et al found that grandfather’s cardiometabolic disease (CMD) was directly associated with grand offspring asthma, while accounting for indirect effects transmitted through parental CMD or asthma, consistently in the RHINE, ECRHS and RHINESSA cohorts (not yet published).…”
Section: Findings To Datementioning
confidence: 99%